Separate reasons for limiting the freedom of contract when choosing the type of transaction - Rasko, Yuliia (ScienceRise: Juridical Science, 2022)
Separate reasons for limiting the freedom of contract when choosing the type of transaction have been studied. For this purpose, the author analyzed the concept and essence of limiting the freedom of contract at the stage of choosing the type of transaction, identified the grounds for limiting the freedom of contract when choosing the type of transaction, compared a number of transactions that, due to their legal nature, significantly limit the freedom of contract, in particular, we are talking about public contracts, contracts of accession, standard and preliminary contracts, as well as contracts with persons who won public bidding. A comprehensive methodology was used to conduct the research, which combined: the historical method, which was used in the analysis of the transformation of legislative approaches to the regulation of freedom of contract; systemic for determining and clarifying the legal nature of the restriction of freedom of contract; the formal-legal method was used in the analysis of the texts of current domestic normative acts, court practice regarding the restriction of freedom of contract; with the help of legal hermeneutics, the content of normative legal acts, regulating the procedure for choosing the type of transaction was clarified; the forecasting method made it possible to develop proposals for the optimal normative-legal regulation of the restriction of freedom of contract; methods of critical analysis became the basis for clarifying the positions of scientists. This methodology made it possible to thoroughly study empirical data, the provisions of the current legislation of Ukraine, as well as the practice of Ukrainian courts. The conducted research made it possible to reach and substantiate a number of conclusions. In particular, that contracts can be both public and accession ones, or only have signs of a public contract or an accession contract. At the same time, when concluding such contracts, the freedom of contract is significantly limited, both with regard to the possibility of the entrepreneur refusing to conclude a public contract, and with respect to the parties joining the accession contract or public contract, who are deprived of the opportunity to determine the terms of the contract. At the stage of concluding a public agreement and an accession agreement, only one of the parties has freedom of action regarding the conclusion. It is substantiated, that the freedom of contract can be limited by a standard contract, which can be both recommended at the level of subordinate legal acts and developed by any participant in civil legal relations. When concluding a preliminary contract, the freedom of the parties is limited temporarily and partially